Using Bifactor Exploratory Structural Equation Modeling to Test for a Continuum Structure of Motivation - Howard, J.; Gagné, Marylène; Morin, A.; Forest, J. (Sage Publications, Inc., 2018)
© The Author(s) 2016. This paper explores the nature of workplace motivation by testing the continuum structure of motivation proposed by self-determination theory through the application of relatively new and advanced methodological techniques. Specifically, we demonstrate the usefulness of the overarching bifactor exploratory structural equation modeling framework in organizational psychology and discuss implications of such models over more traditional confirmatory factor analyses. This framework is applied to responses obtained from 1,124 Canadian employees who completed a multidimensional measure of workplace motivation. The results support a continuum of self-regulation and illustrate the importance of accounting for quality of motivation in addition to its global quantity. Indeed, the results showed that specific types of motivation explained variance in covariates over and above the variance already explained by the global quantity of self-determination. The current study further demonstrates the limitation of the commonly used relative autonomy index and offers alternate conceptualizations of human motivation.